Islamic Education in Singapore: Case Study Madrasah Al-Juneid Al-Islamiyah - Naimah Radzi; Avid Leonardo Sari; Irwandi (GoAcademica Research & Publishing, 2019)
This article explains the development of Islamic education in Singapore, specifically Madrasah al-Juneid al-Islamiyah. The problem: how is curriculum development at Madrasah al-Juneid? And what are the challenges of the future of this madrasa? To answer this problem, the amount of data collected through the method of observation, interviews, and documentation. Data collected were analyzed descriptively-qualitatively. The results show: first, the curriculum at Madrasah al-Juneid initially did not contain pure religion then was expanded by adding general lessons. In learning, study materials are commonly used to approach integration with Islamic teachings. Second, madrassas in Singapore face challenges in the future that are not easy, namely the demands of the world of work, demands for quality, challenges of Western lifestyles, and accusations against Islam as a terrorist religion. Creative madrassas must address all these challenges in developing quality programs so that graduates can compete with graduate schools, can fortify modern secular lifestyles, and can coexist peacefully during Singapore's diverse society.